A genetic cluster of MDR Enterobacter cloacae complex ST78 harbouring a plasmid containing blaVIM-1 and mcr-9 in the Netherlands. Issue 2 (12th May 2021) - Hendrickx, Antoni P A; Debast, Sylvia; Pérez-Vázquez, María; Schoffelen, Annelot F; Notermans, Daan W; Landman, Fabian; Wielders, Cornelia C H; Cañada Garcia, Javier E; Flipse, Jacky; de Haan, Angela; Witteveen, Sandra; van Santen-Verheuvel, Marga; et al.
Abstract: Background: Carbapenemases produced by Enterobacterales are often encoded by genes on transferable plasmids and represent a major healthcare problem, especially if the plasmids contain additional antibiotic resistance genes. As part of Dutch national surveillance, 50 medical microbiological laboratories submit their Enterobacterales isolates suspected of carbapenemase production to the National Institute for Public Health and the Environment for characterization. All isolates for which carbapenemase production is confirmed are subjected to next-generation sequencing. Objectives: To study the molecular characteristics of a genetic cluster of Enterobacter cloacae complex isolates collected in Dutch national surveillance in the period 2015–20 in the Netherlands. Methods: Short- and long-read genome sequencing was used in combination with MLST and pan-genome MLST (pgMLST) analyses. Automated antimicrobial susceptibility testing (AST), the Etest for meropenem and the broth microdilution test for colistin were performed. The carbapenem inactivation method was used to assess carbapenemase production. Results: pgMLST revealed that nine E. cloacae complex isolates from three different hospitals in the Netherlands differed by <20 alleles and grouped in a genetic cluster termed EclCluster-013. Seven isolates were submitted by one hospital in 2016–20. EclCluster-013 isolates produced carbapenemase and were from ST78, a globally disseminated lineage. EclCluster-013 isolates harboured a 316 078 bp IncH12 plasmid carrying the bla VIM-1 carbapenemase and the novel mcr-9 colistin resistance gene along with genes encoding resistance to different antibiotic classes. AST showed that EclCluster-013 isolates were MDR, but susceptible to meropenem (<2 mg/L) and colistin (<2 mg/L). Conclusions: The EclCluster-013 reported here represents an MDR E. cloacae complex ST78 strain containing an IncH12 plasmid carrying both the bla VIM-1 carbapenemase and the mcr-9 colistin resistance gene.